Methods of prenatal education from the perspective of al-qur'an and as sunnah - Mukhlis Fathurrohman; Viki Bayu Mahendra; Fachri Basalamah; Mohamad Ikhwan Amrulloh (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study aims to explore prenatal education methods in three crucial phases according to the perspective of the Qur'an and Sunnah: choosing a spouse, marital relationships, and pregnancy. The research uses a qualitative method with a phenomenological approach, where data is collected from documents and works of scholars and scientists. Phenomenology is used to understand human behavior as a product of how individuals interpret their world. The findings indicate that, in the spouse selection phase, Islam recommends choosing a partner with strong faith, preferably a chaste, fertile woman, not closely related, and not a polytheist. In the marital relationship phase, it is advised to recite a prayer before intimacy, engage in light conversations, and perform ablution before sleep and repeating the act. During pregnancy, prenatal education involves prayer, worship, and Qur'an memorization. Parents are urged to maintain their trust from Allah by educating their child from conception, ensuring both physical and psychological needs are met. For teenagers, learning about marriage before entering family life is essential. Society is encouraged to support a healthy environment for prenatal education, benefiting both parents and the unborn child.